The effect of positive and negative flexibility exercises to develop special strength and effectiveness of 400m youth Hurdlers - Qahtan Abdul Mohsen, Zainab (International Journal of Psychosocial Rehabilitation, 2020)
The research problem lies in: The use of positive and negative flexibility exercises to develop the special strength of the 400m hurdles player, that some young people face weakness and a problem in performance, which requires the need to prepare special exercises for physical and skill numbers using the types of exercises that have resilient strength, flexibility and have the effect on developing and determining the level of physical and skill performance. To develop 400m hurdles, special strength, explosive power and the characteristic velocity of arms and legs. Research aims: 1. Preparing positive and negative flexibility exercises to develop the special force and the effectiveness of 400m youth barriers. 2. Identify the effect of exercises on the development of special strength and the effectiveness of 400m youth barriers. The researcher used the experimental approach, where the research community consisted of players in the 400m youth hurdles event, which numbered (6) for the year 2018-2019. Positive and negative flexibility exercises prepared by the researcher were used. The researcher concluded: The positive and negative flexibility exercises had a positive effect on the development of the special strength of arms and legs and the results of the effectiveness of 400m youth barriers. The researcher recommends: taking the results of this study and circulating it, and emphasizing on equipping the playgrounds with modern training methods, due to the positive impact it achieves on physical development.